Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Prerequisites - p.4 - Factoring Polynomials - Exercises - Page 39: 36



Work Step by Step

$t^2-t-6=t^2+2t-3t-6$ (notice that $-t=2t-3t$) $t^2-t-6=t(t)+2(t)+(-3)t+(-3)2=t(t+2)-3(t+2)=(t+2)(t-3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.